Peran Kompetensi Manajerial Gembala dalam Mewujudkan Visi “Terwujudnya Jemaat yang Misioner” di Gereja KIBAID Jemaat Marinding - Yunita Sombolayuk; Firdaus Firdaus; Setblon Tembang (Sekolah Tinggi Alkitab Jember, 2024)
This research is motivated by the fact that church growth cannot be separated from understanding the importance of the management of a congregational pastor in realizing the church's vision. In this case, the role of the pastor's managerial competence is really needed to achieve the church's vision. KIBAID Church is an evangelical church with the vision of